1993
DOI: 10.2134/jpa1993.0226
|View full text |Cite
|
Sign up to set email alerts
|

Interseeded Forage Legume Potential as Winter Ground Cover, Nitrogen Source, and Competitor

Abstract: Legume winter ground covers may contribute to row crop systems by providing protection from wind and precipitation and by releasing N to the subsequent row crop, but to attain effective size, these legumes must begin growth well before the winter. A 3‐yr study was conducted to evaluate the performance of four commonly used forage legumes interseeded into corn (Zea mays L.). Alfalfa (Medicago sativa L.), yellow sweetclover (Melilotus officinalis Lam.), red clover (Trifolium pratense L.), and alsike clover (T. h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 12 publications
3
29
0
Order By: Relevance
“…Living mulches differ in their ability to establish well in an interseeding situation. For example, Exner and Cruse (1993) found that alfalfa (Medicago sativa L.) and sweet clover (Melilotus officinalis L.) usually established better and produced more cover than either red clover (Trifolium pratense L.) or alsike clover (T. hybridum L.) when interseeded under corn. The competitive ability against weeds is also another important characteristic determining the suitability of a plant species as a living mulch.…”
Section: Living Mulch Speciesmentioning
confidence: 99%
“…Living mulches differ in their ability to establish well in an interseeding situation. For example, Exner and Cruse (1993) found that alfalfa (Medicago sativa L.) and sweet clover (Melilotus officinalis L.) usually established better and produced more cover than either red clover (Trifolium pratense L.) or alsike clover (T. hybridum L.) when interseeded under corn. The competitive ability against weeds is also another important characteristic determining the suitability of a plant species as a living mulch.…”
Section: Living Mulch Speciesmentioning
confidence: 99%
“…Legume intercrops are a potential source of plant nutrients that compliment/supplement inorganic fert ilizers [17]. Legu me intercrops have several socioeconomic [18], and biological and ecological [19,20,21,22,23] advantages compared to sole cropping for small-holder farmers [24]. In addition, certain legumes crops provide food to humans and livestock [17].…”
Section: Introductionmentioning
confidence: 99%
“…1). Previous studies have similarly reported that alfalfa is more competitive with weeds than red clover under semi-arid conditions (Exner and Cruse 1993;Schlegel and Havlin 1997).…”
Section: Weed Biomass In Winter Wheatmentioning
confidence: 86%